Biocompatibility and cellular uptake mechanisms of poly(N -isopropylacrylamide) in different cells - Guo, Z.; Li, S.; Wang, C.; Xu, J.; Kirk, B.; Wu, Jian-Ping; Liu, Z.; Xue, W. (2017)
© SAGE Publications. Thermosensitive poly(N-isopropylacrylamide) is widely used in various biomedical applications including drug delivery systems, gene delivery systems, switching devices, sensors, and diagnostic assays. To promote these clinical applications, it is essential to have a comprehensive understanding of the biosafety of poly(N-isopropylacrylamide) and the interaction of poly(N-isopropylacrylamide) with different cell lines, which has little research until now. In this work, we evaluated the biocompatibility of poly(N-isopropylacrylamide) including cell viability, nitric oxide production, and apoptosis of macrophages RAW264.7, human bronchial epithelial cells, A549, and human umbilical vein endothelial cells in the presence of poly(N-isopropylacrylamide). We have also examined the cellular uptake mechanisms of poly(N-isopropylacrylamide) using endocytic inhibitors and insighted into the intracellular co-localization of poly(N-isopropylacrylamide) using confocal laser scanning microscope. The results showed that poly(N-isopropylacrylamide) had good biocompatibility and could be internalized by these cells. It is macropinocytosis that poly(N-isopropylacrylamide) could be internalized in RAW264.7 cells and caveolae-mediated endocytosis in human bronchi al epithelial cells, A549, and human umbilical vein endothelial cells. In addition, we also evidenced that intracellular poly(N-isopropylacrylamide) was co-localized with lysosome. The study provided important information for the development and clinical applications of poly(N-isopropylacrylamide) in the biomedical field.